Relationship between Transformational Leadership Style and Leadership Thinking of Provincial Administration Leaders - Thanh Nguyen Hai; Tung Trinh Van; Hien Nguyen Thi (Ital Publication, 2021)
Objectives: The transformational leadership style is accepted as suitable for leading administrative agencies to achieve outstanding results and help organizations cope with challenges. Besides, leadership thinking is also considered to have a very important role in leadership performance in administrative agencies. Therefore, the main objective of the study is to explore the relationship between transformational leadership style and leader thinking to organization's performance. Methods: The article focuses on explaining the views on transformational leadership style, healthy thinking, and the relationship between transformational leadership style and leadership thinking, and at the same time points out the current status of transformational leadership style, transformational leadership, leadership thinking as well as this relationship in practice among the leaders of provincial agencies in Vietnam. Descriptive, inductive, deductive, synthetic, and quantitative statistical methods were applied to interpret the results. Findings: Research results show that transformational leadership style, leadership thinking in the team of leaders of provincial agencies is quite average, there is a strong positive correlation between transformational leadership style. In contrast to leadership thinking, a more transformative leadership style means that it requires an innovative leadership thinking. Novelty:The results achieved when applying a transformational leadership style are quite closely related to the application of leadership thinking to solve leadership challenges. Doi: 10.28991/esj-2021-01307 Full Text: PDF